PENGARUH KETERSEDIAAN PRODUK, HARGA DAN PROMOSI TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN (STUDI KASUS PADA ALFAMART CABANG KOTA BATAM TOKO TAMAN KOTA MAS) - Larasati, Dewi; Riki (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2024)
The aim of this research is to analyze the hypothesis analysis that product availability, price and promotion can be determining factors in creating consumer satisfaction through making purchasing decisions for consumers regarding purchasing the desired product at Alfamart Toko Taman Kota Mas. This research used quantitative methods involving 213 Alfamart Toko Taman Kota Mas consumers, including offline and online questionnaire research. The research was carried out using Structural Equation Modeling (SEM) analysis using the IBM AMOS version 23 application. In addition, this research used independent, dependent and intervening variables. The results of the analysis show that product availability, price and purchasing decisions influence consumer satisfaction, respectively, obtaining a CR coefficient value of 4.498, price obtaining a CR coefficient value of 7.607 and purchasing decisions of 10.367. However, the promotion variable shows that it is less significant in influencing consumer satisfaction through purchasing decisions as evidenced by a CR value of 1.819 and a P value of 0.07.